2022
DOI: 10.1093/jeea/jvac038
|View full text |Cite
|
Sign up to set email alerts
|

Gross Capital Flows by Banks, Corporates, and Sovereigns

Abstract: We construct a new quarterly data set of international capital flows broken down by sector - banks, corporates and sovereigns - and demonstrate the importance of distinguishing capital flows by the sector of domestic borrowers and lenders. We document four new sets of facts. First, banks account for the largest part of the external debt (stocks and flows) in advanced economies, whereas in emerging markets, banks, corporates and sovereigns have roughly equal shares. Second, the high correlation between total ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Recent work has extensively documented how shocks to U.S. financial conditions are transmitted to other countries in a so-called global financial cycle (Rey, 2015). While much of this research has focused on bank flows (Bruno and Shin, 2015b,a), changes in U.S. monetary policy and risk appetite are also transmitted via portfolio flows (Forbes and Warnock, 2012;Fratzscher, 2012;Avdjiev et al, 2017). At the same time, it is clear that exposure to the global financial cycle varies across countries (Cerutti et al, 2015;Choi et al, 2017) and over time (Ahmed and Zlate, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has extensively documented how shocks to U.S. financial conditions are transmitted to other countries in a so-called global financial cycle (Rey, 2015). While much of this research has focused on bank flows (Bruno and Shin, 2015b,a), changes in U.S. monetary policy and risk appetite are also transmitted via portfolio flows (Forbes and Warnock, 2012;Fratzscher, 2012;Avdjiev et al, 2017). At the same time, it is clear that exposure to the global financial cycle varies across countries (Cerutti et al, 2015;Choi et al, 2017) and over time (Ahmed and Zlate, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A novel dataset from Avdijev et al ( 2022 ) showed that liability flows were historically high and persistent for the past decade. Again, this is an indication of increased vulnerability in countries that have been receiving these liability flows.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also important to look at liability flows only, i.e., foreigners’ acquisitions and sales of domestic assets. Avdijev et al ( 2022 ) constructed a quarterly dataset splitting flows into liability and asset flows. In Fig.…”
Section: Capital Flows and Indication Of Vulnerabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper sheds light on these issues by using firm-level data on corporate bond issuances for EME companies and analyzing the determinants of foreign currency borrowing. The results show that companies are more likely to issue in foreign currency with more expansionary US 1 E.g., see Gozzi et al (2015), Ayala et al (2017), CGFS (2021), and Avdjiev et al (2022) for descriptions. The issuance of new debt (our focus) is dominated by bonds, while the stock remains dominated by loans.…”
Section: Introductionmentioning
confidence: 99%